Diagnosis of concurrent Rhodococcosis and adenocarcinoma in a cat - Chan, Wei Yee; Selvarajah, Gayathri Thevi (Intas Pharmaceuticals, 2018)
Rhodococcus equi infection in a cat with tumor of maxilla was diagnosed as adenocarcinoma. Diagnostic cytology of discharges from tumor demonstrated numerous macrophages within intracellular basophilic coccobacilli organisms which heighten the diagnosis of R. equi. Bacteria culture and identification assays confirmed a pure isolation of R. equi. The association of neoplasia development and R. equi infection is still poor and further investigation on the epidemiology and evaluation of virulence factors of the organism in feline species is warranted.